History Learning Based on Value of Syech Abdurauf As-Singkili Manuscript to Improve Gender Equality Awareness - Mawardy As Ary Putra (Yupa: Historical Studies Journal, 2018)
Local culture-based education has an important role in character building for students. In a scientific heritage, there are values of wisdom that can be applied in everyday life. The values of this wisdom are reflected in the work of an Acehnese scholar Search Abdurrauf as Singkili, later written in several Manuscripts: Mir'atul Thulab Fe Bag-lubang Ma'ritah Ahkamisy Syar'iyah Lil Mulkil Wahhab and Turjumanul Mustafid. Hence, the history-based learning model of Syech Abdurrauf as a Singkili script was developed. This development is expected to improve students' sense of understanding and awareness about gender equality. From the values listed in Syech Abdurrauf Singkili's text, students are expected to be able to know the value of local wisdom, to develop a pattern of understanding of gender equality awareness both within the scope of school and community, and to raise awareness of equality in Islam. Result: n = 28 and (α) = 0,05, post-test value 0,913, T-test 2,279, n = 200> 0,05, post-test 0,430. There is a significant increase in the study of the development of this model, it is expected that with this model of learning history able, develop a gender equality awareness of the students.